(untitled) (Kinesiology, 2017)
The aim of this study was to compare activity patterns between male and female wheelchair tennis (WT) matches. Sixteen singles international WT matches (eight male and eight female) were analysed. Each match was recorded and analysed according to the following variables: total match time (minutes), total set time (minutes), effective playing time (%), total resting time (%), working time: resting time ratio (W:R), resting time between points (seconds), rally duration (seconds), points per set, shots per set, shots per rally, bounces per point, and time between shots (seconds). A Mann-Whitney U test was used to compare between the genders and Wilcoxon test was used to compare variables with the type of point (non-game point opportunity – NGO, and game point opportunity – GO). Female matches showed higher values (p<.05) in rally duration, bounces per point, and frequency of shots than male matches. Both genders spent more time between points in GO than in NGO situation. The findings indicate that male and female players play in a different way, and these differences should be taken into consideration by the WT coaches. Key words: adapted tennis, gender, match activity